= (-1)^2 (d^2/ds^2) laplace(cos(t)) = (d^2/ds^2) (s/(s^2+1)) = (d/ds) [-2s^2(s^2+1)^-2 + (s^2+1)^-1] = 8s^3/ (s^2+1)^3 - 6s/(s^2+1)^2 thats the answer i got but the answer in the book says (2s^3 - 6s)/ (s^2+1)^3 where did i go wrong?
Follow Math Help Forum on Facebook and Google+
Originally Posted by linalg123 = (-1)^2 (d^2/ds^2) laplace(cos(t)) = (d^2/ds^2) (s/(s^2+1)) = (d/ds) [-2s^2(s^2+1)^-2 + (s^2+1)^-1] = 8s^3/ (s^2+1)^3 - 6s/(s^2+1)^2 thats the answer i got but the answer in the book says (2s^3 - 6s)/ (s^2+1)^3 where did i go wrong? You didn't go wrong anywhere!! Just combine the two fractions you got to get the desired result!!
ughh..duhhh.. thanks
View Tag Cloud